Effects of herbal supplements on milk production quality and specific blood parameters in heat-stressed early lactating cows - Saleh, Ahmed Ali; Soliman, Mahmoud Mohamed; Yousef, Mohammed Farid; Eweedah, Nabil Mohammed; El-Sawy, Hanan Basiouni; Shukry, Mustafa; Wadaan, Mohammad A. M.; Kim, In Ho; Cho, Sungbo; Eltahan, Hossam M. (Frontiers in Veterinary Science, 2023)
The present study explored the influence of supplemental herbal mixtures on cow milk production quality and blood parameters in dairy cows under high ambient temperatures. Thirty Holstein cows were randomly assigned into three experimental groups of ten each. The first control group was supplied with the commercial basal diet, whereas two treatment groups were provided with the commercial basal diet supplemented with 50 and 100 g/head/day of the herbal mixture, respectively. The results showed that a mixture of herbal supplementation did not influence weekly milk production. Milk total fat, triglyceride, and total protein values were not affected (P < 0.05) in cows fed on basal diets supplemented with herbal mixture; however, milk cholesterol was decreased significantly by 100 mg/head/day of the herbal mixture. On the other hand, lactose content was increased by the herbal mixture. Furthermore, the level of total cholesterol in serum was decreased by the mixture of herbs at a high level, while serum prolactin, cortisol, GOT, and GPT were not affected. Regarding fatty acids (C18, C18:1 (c9), 18:1 (c11), 18:2 (c9, c12), 18:2 (t9, t12) and CLA (c9, t11)), there was no significant variation between the groups. Meanwhile, both C19:00 and 18:3 (c6, c9, c12) were noticeably higher (P< 0.05) in the group that received 100gm, followed by 50 mg, compared to the control. In conclusion, the supplement with a herbal mixture positively affected milk quality, milk fatty acid profile, and serum cholesterol levels.